Expanding the Patent Law of the People’s Republic of China: A Proposal for Patent Protection of Computer Programs - Syz, Jing-Kai (Columbia Journal of Asian Law, 1991)
When the People’s Republic of China (PRC or China) promulgated a patent law in 1984, some viewed the new law as an effort to protect and encourage inventions, to stimulate international exchanges, and to facilitate technology transfers to the PRC Although it is apparently successful and generally complete, the Patent Law largely dodges the important subject of protecting computer programs. The PRC government has decided to permit computer software copyrights, which may imply a denial of patentability of computer programs. Because computer programs are a relatively new and increasingly important technology, many countries, developed as well as developing ones, have encountered legal and intellectual difficulties in dealing with programs. The PRC is no exception. This note argues that the PRC should bring computer programs within the structure of its Patent Law, even though copyright protection is concurrently available. As a foundation for this proposed legal reform, Part II of the note places the Chinese patent system in its historical and contemporary contexts, viewing computer program protection from the Chinese economic, ideological, and political perspectives. Part II then examines two major methods for protecting computer programs: copyright and patent. This note contends that patent protection of programs is necessary in the PRC because copyright protection is too limited in scope. Furthermore, if the PRC’s copyright system does not require full disclosure, society would lose the benefits from learning new technology. In addition, computer program patents are common among developing countries, and they are particularly appropriate for the Chinese economy. Having shown the theoretical attractiveness of patent protection, the note proceeds in Part IV to apply the Chinese Patent Law to programs. The note argues that computer programs are proper subject matter within the existing patent framework, and that the Chinese Patent Law is designed to minimize administrative difficulties and to prevent patents from disrupting the progress of technology. Finally, in Part V, the note concludes that copyrights should protect the expressive aspects of computer programs, while the functional features of programs should be patentable.